Zakat Investasi Reaktualisasi Fikih Kontemporer dalam Ekosistem Ekonomi Syariah - Siti Nuranisya; Cucu Susilawaty (SPT. haria Journal and Education Center Publishing, 2026)
This study examines the urgency of investment zakat as an Islamic financial instrument from a contemporary Islamic economic perspective. Etymologically, zakat means al-numuw, which signifies fertility, growth, and development. However, in practice, zakat now faces the challenges of the diversification of modern financial instruments that have not been comprehensively documented in classical jurisprudence literature. Through a literature study, this research analyzes the classification of productive assets and the re-actualization of Islamic law regarding zakat mechanisms on investment assets, such as stocks and industrial sectors. The results indicate that investment zakat, derived from accumulated profit margins or net returns, has transformed into an integral pillar of the modern economic ecosystem. Its position is no longer merely a ritual instrument but a strategic financial power that contributes directly to macroeconomic stability. Furthermore, this study affirms that optimizing the governance of investment zakat is a crucial systemic solution for mitigating national economic issues, particularly in addressing poverty, income disparity, and unemployment. Thus, investment zakat proves to be a fundamental and adaptive financial instrument to cover the potential of new wealth emerging from various contemporary economic activities. Keywords: Zakat, Islamic Investment, Contemporary Fiqh, Macroeconomics, Wealth Distribution.